Documentary method and praxeological sociology of knowledge in the interpretation of pictures - Ralf Bohnsack (methaodos.revista de ciencias sociales)
Under the name “picture science“ an access to the internal logic of the picture in demarcation from verbal language and text was demanded first from side of the spiritual sciences – in broad accordance among prominent authors from this field. Social sciences and sociology as empirical sciences especially have to face the challenge of implementing these demands methodically and theoretically according to their epistemological standards. Concerning the groundbreaking Iconology developed by Panofsky a stronger consideration of the formal composition of the picture is demanded from side of the history of arts. From a mere sociological perspective the following has to be claimed in addition: the iconological access to the picture with its praxeological perspective on the modus operandi of its production by Panofsky’s category of the habitus had overcome the iconographic perspective, which is bounded to the common sense with its (methodically not justifiable) ascriptions or imputations of intentions and motives to the picture producers. In the further development of the praxeological perspective on the one hand a differentiation of the category of the habitus regarding photography seems to be necessary – by distinguishing between the habitus of the picture producers behind the camera from those in front of it. On the other hand it seems important to transcend the category of the habitus in direction of incongruencies and ambiguities which are constitutive for the frames of orientation of the picture producers and thus the semantic of the picture. This will be demonstrated empirically in this work by the interpretation of advertising pictures on base of the Documentary Method with respect to the category of the pose, which appears as a de-contextualization of relevant gestures.